Welfare effects of policy-induced rising food prices on farm households in Nigeria - Shittu, Adebayo M.; Obayelu, Oluwakemi A.; Salman, Kabir K. (International Food Policy Research Institute, 2015)
Domestic policies in Nigeria have been linked to high, volatile, and rising food prices in the country. In light of these linkages, this paper empirically examines the transmission of key monetary policy variables to domestic food prices and the resulting welfare impacts. Estimates of policy-induced price changes from estimated cointegrating relations between commodity prices and policy variables as well as demand elasticities from estimated quadratic almost ideal demand system (QUAIDS) of households’ consumption expenditures, were employed to estimate the welfare impact (compensating variation) of the policy-induced price changes. The study found that government management of exchange rates and money supplies as well as withdrawal of subsidies on petroleum products have been the main driver of rising food prices in the country. While the average farm household benefited from these price increases, with the mean (median) compensating variation estimated -7.8% (-0.2%) of the household budget, a sizeable proportion (44.1 – 55.5%) of the households suffered welfare losses from various policy induced price changes. These include, notably households of smallholders (14.3 – 84.2%) and female-headed households (34.1 – 62.8%). Overall, while domestic policy actions relating to money supply and subsidy removal were Kaldor–Hicks efficient, exchange rate devaluation was not.